18S rRNA V9 taxonomic classifier ... - Anderson, Sean; Silliman, Katherine; Thompson, Luke (Zenodo, 2023)
18S metabarcoding databases and naive-bayes classifier specific to the V9 region. Built from the PR2 v5.0.0 database using Qiime2 (version 2021.2). Primers used: 1391f: GTACACACCGCCCGTC EukBr: TGATCCTTCTGCAGGTTCACCTAC File Description pr2_seqs.qza |. Full length PR2 v5.0.0 sequences pr2_tax.qza | Taxa for PR2 v5.0.0 database refseqs_V9.qza. | Sequences for 18S V9 (primers 1391f, EukBrr), extracted from PR2 SSU v5.0.0, generated by qiime2-2021.2 (forward compatible) classifier_V9.qza | Unweighted (uniform) naive-bayes classifier for 18S V9 extracted from PR2 SSU v5.0.0, generated by qiime2-2021.2 ... : "This work was supported by award 21392 to the Northern Gulf Institute from NOAA/OAR Ocean Acidification Program." ...